BETWEEN TRADITION AND MODERNITY: THE RELEVANCE OF BOARDING SCHOOL VALUES IN FORMING STUDENTS' OBEDIENT BEHAVIOR - Mukarromah, Azizeh; Manshur, Umar; Syafaat, Imron Nur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to explore the role of pesantren culture in shaping the obedient behavior of santri at Pondok Pesantren Al Maliki 2. The method used in this study is qualitative with a case study approach. Data collection was conducted through observation, in-depth interviews, and documentation. The results show that the pesantren culture, which includes the practice of religious rituals, discipline, responsibility, and social values, has a significant influence on the formation of obedient behavior among the santri. Santri who are accustomed to a religious and orderly environment exhibit stronger obedience both in the context of religious activities and in daily life. These findings underscore the importance of the pesantren's role in shaping santri with good character and morality. The implications of this study highlight the need for pesantren to continuously strengthen the culture of obedience through ongoing supervision and guidance to ensure that pesantren values are upheld by santri, both within and outside the pesantren environment.